Designing a Test Instrument to Reveal Students' Reasoning Abilities on Archimedes' Law - Luh Sukariasih; Erniwati; Hunaidah (Postgraduate, University of Mataram, 2026)
Visuo-haptic simulator-based learning can help students understand the relationship between buoyancy and the volume of displaced fluid. In this study, students experienced a physical simulation of an upward force, which has been shown to improve conceptual understanding and reduce misconceptions commonly found in traditional classrooms. This study aimed to design a test instrument that could reveal in detail students' reasoning abilities related to Archimedes' Law, specifically regarding the phenomena of floating, levitating, and sinking. The study used a qualitative approach through two stages of testing administered to 31 first-year physics students who had taken a basic physics course. The initial test used the five-block problem developed by Loverude to identify students' reasoning patterns, which mostly showed misconceptions, such as determining the final position of an object based on mass rather than density. Based on this analysis, four diagnostic questions were developed to explore students' understanding of the differences between density, buoyancy, and the application of Newton's Laws in the context of fluids. The test results showed that although students had some correct knowledge, they often failed to apply it correctly, especially in cases involving more than one object or calculating the volume of displaced fluid. Based on these findings, the instrument was developed into six tested and validated items capable of comprehensively assessing students' reasoning abilities and conceptual understanding. This instrument can be used by educators to diagnose and correct student misconceptions related to Archimedes' Law.